DETECTION OF BACTERIAL URINARY TRACT INFECTIONS IN PREGNANT WOMEN WITH GESTATIONAL DIABETES AND STUDYING THE ROLE OF SOME VIRULENCE FACTORS OF S. AUREUS IN THOSE INFECTIONS - Staar Mohammed Qader (European Science Publishing, 2024)
UTIs are prevalent among a significant proportion of the population. At some stage in their life, over half of all women will have a urinary tract infection (UTI); one-third of these instances require antibiotic therapy.
Keywords: UTI, pregnancy, gestational diabetes, virulence factors, S. aureus detection.